(untitled) (Janaki Medical College Journal of Medical Science, 2022)
There are many social, economic, political and cultural factors that affect the ability of developing and resource poor countries to provide adequate oral health care for its people, including children and adolescents. Untreated carious teeth are common findings in African children, and Restorative index and Met Need Index among children and adolescents are very low. This could be as a result of limited access to oral health services in terms of cost, accessibility, awareness, acceptability and availability. Access tooral health care service among children for preventive, restorative, rehabilitative and curative purpose is important for optimal oral health and wellbeing of a child. Access to oral health services is limited in African countries, and carious teeth are often left untreated. The challenges associated with access to oral health care are common in African countries. They are faced with continuous oral health care delivery and access problems with variation in the availability of dentists between countries and poor funding for oral health. Most of the dentists that practice in African region are mostly delivering oral health services to children and adolescents in urban areas than rural areas. This can contribute to oral health inequalities among children and adolescents in slum areas, riverine areas, rural and remote areas. After searching articles from electronic databases, the aim of this article is to review the burden of dental caries, the dentist to patient ratio, Restorative index and Met need index of children and adolescents.